2023
DOI: 10.1111/ffe.13968
|View full text |Cite
|
Sign up to set email alerts
|

The role of loading mode on the property degradation of adhesives at high temperatures

Abstract: Despite existing studies on the effects of temperature on the behavior of bonded joints, the role of loading mode and test type (strength, fatigue, and fracture tests) on the rate of degradation of adhesive/joint properties at high temperatures has not been adequately investigated. The aim of the current study is to determine if adhesives experience the same rate of degradation at high temperature when they are subjected to different mode mixities. To do so, an epoxy adhesive was subjected to strength, fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Then, at 150°C, G IIC decreased by about 41% in relation to the value obtained at 100°C, and finally a drastic drop was observed at a temperature above T g . The effect of temperature in G IIC was also investigated by Castro Lopes et al 28 The authors reported that G IIC value is higher at 50°C than at room temperature, which is in accordance with the work of Banea et al 32 Anyway, since creep phenomenon was not analysed in those situations, further research in this area is warranted to provide a more comprehensive understanding of adhesive joint behaviour under creep conditions.…”
Section: Creep Characterisationsupporting
confidence: 71%
See 1 more Smart Citation
“…Then, at 150°C, G IIC decreased by about 41% in relation to the value obtained at 100°C, and finally a drastic drop was observed at a temperature above T g . The effect of temperature in G IIC was also investigated by Castro Lopes et al 28 The authors reported that G IIC value is higher at 50°C than at room temperature, which is in accordance with the work of Banea et al 32 Anyway, since creep phenomenon was not analysed in those situations, further research in this area is warranted to provide a more comprehensive understanding of adhesive joint behaviour under creep conditions.…”
Section: Creep Characterisationsupporting
confidence: 71%
“…Banea et al 27 investigated the effect of different temperatures on G IC , showing that for joints subjected to quasi static loading conditions G IC is temperature independent if the test is conducted below the glass transition temperature (T g ) of the adhesive while, for temperatures above the T g , the value of G IC dropped drastically. A recent work 28 also investigated the effect of temperature on the G IC of adhesives. They showed a degradation in this property by increasing the temperature.…”
Section: Creep Characterisationmentioning
confidence: 99%
“…Lopes et al [ 26 ], while studying the temperature effect on an epoxy adhesive subjected to different mode-mixities, also concluded that the temperature sensitivity was more noticeable in tensile loading conditions when compared to shear mode and that the tensile fracture energy dropped with increasing temperature. Santos et al [ 22 ] also found that an increase in temperature from 23 °C to 60 °C led to a decrease in strength and ductility for the adhesive in the study, which translated into a huge decrease in fracture toughness in mode I.…”
Section: Resultsmentioning
confidence: 99%
“…Adhesive bonding is also useful for bonding similar and dissimilar materials of varying thicknesses [18,19]. Considering this level of complexity and the variety of applications, adhesive systems are susceptible to various mechanical failure modes within the different loading conditions [20]. Hence, focusing on the improvement of the performance and investigating the failure modes of adhesively bonded joints in composite structures should be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…The fatigue life of a composite adhesive joint is impacted by the distribution of stresses along the adhesive and adherends, as well as their interface, which is a function of various parameters, including joint configurations, material properties of adherends and adhe-sive [28], the service temperature [20,29], the humidity level [30], the manufacturing process, and associated surface treatment [31]. The fatigue life can be controlled by modifying these parameters, such as hybridizing the adherends and adhesive [32,33], incorporating additive particles [34], and adjusting the configurations [35].…”
Section: Introductionmentioning
confidence: 99%